Evaluasi Penerapan Sistem Mutu Safe Quality Food: Lesson Learned di Industri Pangan PT XYZ - Siti Nurjanah; Muhammad Fahrizal Setiawan (Jurnal Mutu Pangan : Indonesian Journal of Food Quality, 2019)
Safe Quality Food (SQF) is food safety and quality management system that apllied food safety principles (US National Advisory Committee on Microbiological Criteria for Food) combined with HACCP system (Codex). SQF standards contains of Module 2 and another modules that suitable for specific porpuses industry. The objectives of this research were to calculate the fulfillment 9 clauses of SQF Module 2 requirements and its corrective actions to increase the effectiveness of SQF implementation. PT XYZ has been certified SQF management system level 3 for Module 2 and evaluated implementation of this system regularly. This research was conducted in steps: assessment of implementation SQF 7.2 (Module 2), analysis of gap using GAP Analysis Tool, and evaluation of corrective actions for continuous improvement process. Quantitative data showed that PT XYZ complied 100% for 6 out of 9 clauses of SQF 7.2 Module, and 3 others clauses have implemented 93% (clause of document control and record), 99% (clause of attaining food safety and quality), and 94% (clause of training). Corrective action have decided and implemented effectively. Corrective action were making distribution document's SOP, matrix of hazard significance determination refers to Codex, implementing pre and post-test for evaluating staff's competencies, and integrated audit system between SQF and ISO 9001:2015 using iAuditor application.